THE EFFORT TO REPAIR TODDLER’S NUTRITION DUE TO LACK OF VITAMIN A - Andriyani, Fatika (Journal of Ultimate Public Health, 2017)
Lack of Vitamin A (KVA) is still a widespread problem throughout the world, especially in developing countries and can occur at any age, especially during growth. KVA in the body can cause various types of diseases that are "Nutrition Related Diseases" which may involve a wide range of anatomy and function of organs such as lowering the immune system and lowers epitelisme skin cells .One of the impact of less in Vitamin A is an eyes abnormality, which generally occurs in children aged 6 months - 4 years and become a major cause of blindness in developing countries. Toddlers Malnutrition in 2013 amounted to 2,475 (0.30%) compared to the year 2012 with number of 1,131 (0.06%). The Incidence of malnutrition are more prevalent in infant girls (1,305 cases) than infant boys under five years old (1,170 cases). While the percentage of Toddlers malnutrition is getting treatment in 2013 amounted to 100%.